Literature Study on the Application of Financial Accounting Standarts for Micro, Small and Madium-Sized Entities (Sak EMKM) to Assess the Fairness of UMKM Financial Statements - Yolanda, Nabila; Izzati, Dina; Zahrani, Vista; Delani, Maisya; Aliah, Nur (Indonesian Journal Publisher, 2024)
The implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in Indonesia aims to enhance the transparency and accountability of MSME financial statements. Despite its design to cater to MSME characteristics, many businesses struggle with full implementation. This study highlights several challenges, including a lack of understanding of accounting principles, insufficient skilled personnel, and inadequate socialization and training. Consequently, many MSMEs rely on simplistic recording methods that fail to comply with SAK EMKM, leading to less informative financial statements. To foster better adherence to these standards, collaboration among accounting institutions, the government, and MSMEs is essential for education and training initiatives. By improving their understanding of SAK EMKM, MSMEs can enhance the quality of their financial reporting, thereby facilitating better access to financing and strengthening their contributions to the national economy.